PLANKTON: A New Theory of Organization for the 21st Century - Simonovich, Javier; Sharabi, Moshe; Arian, Ofer (Advances in Social Sciences Research Journal, 2017)
Theories of the organization were extensively researched during the 20th century and are still important at 21st century. We explain the behavior of organizations and then propose an innovative and creative perspective through the pronunciation of PLANKTON organization theory, which responds to the new needs and developments of organizations human services in the technological and global world in which we live. The organizational PLANKTON theory is a theoretical perspective that has been developed by the authors during the last fifteen years as a result of an intensive advisory work to human service organizations and College teaching at the Human Services, Sociology and Political Science departments in Israel. PLANKTON theory of organization proposes eight theoretical concepts through which the understanding of the theory is possible. The eight concepts are planning, learning, achievable, norms, knowledge, technology, opportunity and natural.